Analysis of the needs for integrated mathematics and natural sciences modules of the independent curriculum as a learning resource for PGSD UNP Kediri students - Farida Nurlaila Zunaidah; Nurmilawati, Mumun; Violia, Zahara (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this study was to analyze the need for learning resources in the form of MIPA modules integrated with the independent curriculum. The method used in this research is qualitative by using a research instrument in the form of a questionnaire on the needs of MIPA learning resources on the platform google form. Data collection technique by distributing questionnaires to respond to the needs of MIPA learning resources for 3rd semester students of PGSD Study Program, Nusantara University PGRI Kediri. Data analysis technique by analyzing the results of the needs response questionnaire. Based on the questionnaire analysis of the results of the response to the need for MIPA learning resources, it was found that students needed learning resources in the form of MIPA modules. The MIPA module is integrated with the independent curriculum so that later the material presented in the module is also in line with current needs in the field